Leisure-time physical activity as a key protective factor against cognitive decline in older adults: an isotemporal substitution analysis - Flávio Rodrigues Duarte; Lucas Lima Galvão; Rizia Rocha-Silva; Sheilla Tribess; Rafaela Gomes dos Santos; Douglas de Assis Teles Santos; Jair Sindra Virtuoso Júnior (Cadernos de Saúde Pública, 2024)
Abstract: This study aimed to test hypothesized effects of replacing sedentary behavior with moderate-to-vigorous physical activity, sleep, and different domains of physical activity by equivalent amounts on suggestive cognitive decline in an older adult population. This was a cross-sectional study including 473 older adults aged ≥ 60 years. Cognitive decline was assessed using the Mini-Mental Health Examination. Physical activity, its different domains and the time of exposure to sedentary behavior were assessed using the International Physical Activity Questionnaire. For data analysis, two isotemporal substitution models were constructed using Poisson regression. The first model tested the effect of sleep time, sedentary behavior, and moderate-to-vigorous physical activity on cognitive decline. The second model was used to determine the effect of physical activity domains (leisure, work, transport, and home), sleep time, and sedentary behavior on cognitive decline. Physical activity during leisure time was protective against cognitive decline among all domains tested, replacing sedentary behavior, sleep, and transport. Conversely, substitution of the leisure domain for sedentary behavior, sleep, and transport was considered a risk factor for cognitive decline. Leisure time proved to be a strong protective factor in reducing the risk of cognitive decline, and it is necessary to encourage and stimulate public policies that include it.